2022
DOI: 10.3389/fcimb.2021.761153
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vaginal Gardnerella and Tubal Pregnancy in Women With Symptomatic Early Pregnancies in China: A Nested Case-Control Study

Abstract: The early diagnosis and treatment of ectopic pregnancy (EP) remains a major challenge. Despite a known link between vaginal microbiota and female reproductive health, few studies have focused on the association between vaginal microbiota and pregnancy location. This nested case-control study aimed to characterize the vaginal microbiota in tubal pregnancy (TP) among symptomatic women in early pregnancy. Women with symptomatic early pregnancy of unknown location (PUL) were included in this study. 16S rDNA gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Prolonged cases of BV have been associated with a predisposition to conditions like pelvic inflammatory disease, ectopic pregnancies, and induction of early labour if pregnant. In a case-control study by Zhang et al (2021), a cohort of females with confirmed tubal pregnancies exhibited higher concentrations of Gardnerella over two years [ 6 ]. In this case, we can appreciate the development of ectopic pregnancy, which likely developed due to recurrent and refractory BV.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged cases of BV have been associated with a predisposition to conditions like pelvic inflammatory disease, ectopic pregnancies, and induction of early labour if pregnant. In a case-control study by Zhang et al (2021), a cohort of females with confirmed tubal pregnancies exhibited higher concentrations of Gardnerella over two years [ 6 ]. In this case, we can appreciate the development of ectopic pregnancy, which likely developed due to recurrent and refractory BV.…”
Section: Discussionmentioning
confidence: 99%